“I don't have to be perfect; I can just do my best and I have noticed that it's enough”: A Mixed Methods Study Exploring the Effectiveness of a Parenting Intervention for Parents with Anxiety in Reducing Parental Perceptions of Child Anxiety - Williams, Isabel (2024)
Aim: To explore the effectiveness of an adapted parenting intervention, Parenting with Anxiety: Helping Anxious Parents Raise Confident Children (PWA), delivered by a Trainee Educational Psychologist (TEP), in reducing parental perceptions of child anxiety. Subsidiary to this, the research aimed to explore parental perceptions of the intervention.